2007
DOI: 10.1532/ijh97.06173
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Clinical Characteristics of Acute Myeloid Leukemia Associated with Disseminated Intravascular Coagulation

Abstract: Disseminated intravascular coagulation (DIC) is one of the important complications to develop in patients with acute myeloid leukemia (AML). While acute promyelocytic leukemia (APL) is a strong risk factor for DIC, other clinical features have not been fully defined. We retrospectively analyzed 161 consecutive adult patients with de novo non-APL AML. DIC was diagnosed in 52 patients (32%); 28 patients at diagnosis and 24 soon after the initiation of induction chemotherapy. Leukocyte counts, C-reactive protein,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
42
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 18 publications
5
42
1
1
Order By: Relevance
“…In patients with AML, decreased fibrinogen levels are frequently associated with disseminated intravascular coagulation, which is known to be associated with an increased risk of severe bleeding. [34][35][36] Life-threatening bleeding was the second major reason for ICU admission in our cohort of AML patients, and was found to be associated with a poor outcome. Our observations are in line with previously published data showing that bleeding is one of the primary causes of an ICU admission in critically ill patients with hematologic malignancies, [37][38][39][40][41] and particularly in patients with AML.…”
Section: Discussionmentioning
confidence: 82%
“…In patients with AML, decreased fibrinogen levels are frequently associated with disseminated intravascular coagulation, which is known to be associated with an increased risk of severe bleeding. [34][35][36] Life-threatening bleeding was the second major reason for ICU admission in our cohort of AML patients, and was found to be associated with a poor outcome. Our observations are in line with previously published data showing that bleeding is one of the primary causes of an ICU admission in critically ill patients with hematologic malignancies, [37][38][39][40][41] and particularly in patients with AML.…”
Section: Discussionmentioning
confidence: 82%
“…10,[22][23][24] In previously published reports, the following risk factors for developing DIC were identified: high levels of C-reactive protein, high leukocyte counts, negative expressions of CD-13 and HLA-DR, and cytogenetics with a normal karyotype or 11q23 abnormality. 22 None of these previous studies reported on thrombosis or bleeding complications in relation to DIC. We found a comparable DIC incidence (8.5% younger cohort and 6.3% elderly cohort) in our series of patients.…”
Section: Discussionmentioning
confidence: 99%
“…DIC has often been associated with bleeding manifestations in AML cases, especially in APL cases [3][4][5][6][7][8]. DIC also occurs as a devastating complication in patients with other types of AML.…”
Section: Discussionmentioning
confidence: 99%
“…Although DIC also occurs as a devastating complication in patients with other types of acute myeloid leukemia (AML), it develops less frequently [3][4][5][6][7][8]. The release of procoagulant materials or enzymes from blasts or the fibrinolytic activity of leukemic cells themselves has been implicated in DIC [5,9,10].…”
Section: Introductionmentioning
confidence: 99%